Analysis of Word Formation in ‘Made You Look’ Song Lyrics by Meghan Trainor - Panduwati, Lulu; Evert H Hilman (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study examines word formation trends in contemporary popular music through an analysis of Meghan Trainor’s song “Made You Look.” The aim is to explore how linguistic creativity in pop lyrics contributes to emotional expression and social interaction. Utilizing a qualitative approach, specifically discourse analysis, the research investigates how word formation processes shape cultural identity and audience engagement. The study relies on theories from Levitin (2006), Lieber (2009), and Yule (2010) to understand the cognitive, morphological, and structural aspects of language in music. Findings indicate that the lyrics of “Made You Look” incorporate various word formation processes, particularly clipping (3), coinage (1), derivation (1), compounding (4), and conversion (2). Examples such as “nothin’” (clipping), “Gucci” (coinage), and “‘bout” (clipping) reflect the informal, conversational tone characteristic of pop music. These linguistic choices enhance relatability, reinforce cultural identity, and contribute to the song’s rhythmic appeal. Additionally, the study highlights how Trainor’s use of word formation aligns with sociolinguistic trends in informal speech, particularly within African American Vernacular English (AAVE). The study concludes that word formation in pop lyrics is not merely stylistic but also serves as a strategic linguistic tool for self-expression, audience connection, and cultural representation. This research contributes to the broader understanding of language evolution in media and popular culture.